Phenolic contents and antioxidant activity of barhi date palm (Phoenix dactylifera L.) kernels extracts - Mahmud, Israa Ali; Mirghani, Mohamed Elwathig Saeed; Al-Khatib, Ma'an Fahmi Rashid; Shahabuddin, Munira; Assaf, Areej (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Consumption of foods rich in phytochemicals with potential antioxidant properties can reduce the risk of various degenerative diseases such as cancer, atherosclerosis, diabetes, and aging. Several plant materials have been studied as sources of potentially safe natural antioxidants such as vegetables, fruits, cereals, barks, roots, spices and herbs. However, relatively less information is available on the antioxidant potentials of food processing products and agro-industrial wastes which are usually discarded in huge quantities. Some studies reported that the peel and kernel fractions of some fruits have been found to possess higher antioxidant activity than the pulp fraction based on their ferric reducing/antioxidant power (FRAP) values. Accordingly, the search for new natural antioxidants in wastes such as peels, brans and kernels has taken a very high attention in the last decade. The kernels obtained after date processing constitute a very cheap source for the extraction of antioxidant phenols, which makes them suitable for the preparation of dietary supplements, or in the production of phytochemicals, providing an important economic advantage through increase the utilization of date kernels while also additive value will be added to the residue. The aim of this research was, therefore, to investigate the effect of different extraction solvents on the phenolic content and antioxidant activity of Barhi date palm kernels (DPK). The solvent systems used were methanol, ethanol, acetone and distilled water. The antioxidant activity of the Barhi DPK was evaluated using ferric-reducing antioxidant power assay (FRAP), 1,1-diphenyl-2-picrylhydrazyl free radical-scavenging capacity (DPPH), 2,2- azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) and total phenolic compounds (TPC).